The catalytic solventless synthesis of disiloxane using gold nanoparticles supported by reduced graphene oxide / Muhammad Nur Iman Amir - Muhammad Nur Iman , Amir (2023)
Most of the synthetic chemical reactions are involved in the application of various organic solvents. However, some of the toxic solvents are mainly used specifically in the chemical industry and research laboratory. These toxic solvents have caused major environmental pollution and degradation of worker’s physical and health. Therefore, the green chemistry approach is important to provide an alternative chemical process either by reducing or eliminate the usage of harmful solvents during reaction. Subsequently, the key aspect of the green artificial method is to utilize sustainable products, safe chemical and to carry out the chemical process under solventless conditions. Consequently, the catalytic design is important to produce an efficient and effective catalyst that can produce high conversion and selectivity in a solventless reaction. This project was focused on the synthesizing and characterizing gold (Au)-based catalyst because Au has electrochemical stability in strong acid conditions and remarkable selectivity for dehydrogenative coupling reaction. Au synthesized in this project was present as nanoparticles sized as confirmed by XRD and HR-TEM analysis. It was found that, the gold nanoparticles (AuNPs) have good interaction with reduced graphene oxide (rGO) support as XPS analysis demonstrated the interaction of Au-O-C. The catalyst of AuNPs/rGO was synthesized with different molarity of Au solution by using trisodium citrate (Na3C6H5O7) as a reducing and capping agent in one pot synthesis method prior to its solidification in freeze drier process. Then, the catalyst was tested in both solvent and solventless in oxidation reaction of dimethylphenylsilane (DMPS) into 1,3-diphenyltetramethyldisiloxane. The reaction with benzaldehyde solvent showed 100% conversion after one hour whereas reaction without solvent showed 70% conversion after 12 hours because the substrate’s viscosity in solventless reaction was higher than solvent reaction. However, the solventless reaction showed 100% selectivity compared to 84% selectivity in solvent reaction. Different reduction agent catalysts were tested and reaction parameter of the catalyst weight, Au concentration and temperature had been varied in the reaction. It was found that 4 wt% mM AuNPs/rGO was the optimizing catalyst in dehydrogenative coupling of hydrosilanes. The catalytic activity of 4 wt% mM Au was higher than other Au concentration possibly due to lower precursor deposition compared to higher Au concentration of catalyst that led to lower catalytic activity. The catalytic activity of AuNPs/rGO synthesis from sodium borohydride (NaBH4) reduction agent was higher than citrate reduction agent because NaBH4 is a stronger reduction agent that possibly created strong bonding between BH4‾ with the core of AuNPs. The AuNPs/rGO catalyst reusability was tested for five times with small decrease of conversion because no significant functional and structure of the catalyst was changed based on FTIR and XRD analysis.